The Hop : a novel - Clarke, Diana (Harper, an imprint of HarperCollinsPublishers, 2022)
The story of a poor scrappy girl from rural New Zealand who grows reluctantly into a sex icon, the face of a movement, and a mother, all at the same time. Kate Burns grows up wanting attention from her Ma, but her Ma wants only money and Kate learns how to get both. She and her childhood friend, Lacey, run kissing lessons for cash in the janitor's closet of Fenbrook High, and just like that, they find themselves in the sex work industry. From there, they go on to work at The Purple Panther, a strip club in Auckland. When Ma dies of cancer, Kate discovers that the men her Ma was always inviting over to their home were, in fact, clients. Ma was no stranger to sex work either. Following in Ma's footsteps, Kate heads to Nevada where she picks up a job at America's most prestigious brothel: The Hop. In her new life as a Bunny, Kate searches for an identity she can perform -- the other Bunnies include a goth, a housewife, a cheerleader, a rebel, not to mention Betty, a trans beauty queen, Mia, a Japanese cosplayer, and Rain, a dominatrix. Kate becomes Lady Lane. The girls at The Hop are more fantasy than fact, and performance is always more perfect than the real. Kate is a natural and quickly rises through the ranks to become the bestselling Bunny and the owner, Daddy's favorite. But when ten street hookers are killed in a nearby city, just bodies with no names, Lady joins her sister Bunnies in mourning and begins to see things in a new light. Lady's success breeds scandal and unwanted fame, deeply affecting her, transforming her life and The Hop forever.